2007
DOI: 10.22621/cfn.v121i2.443
|View full text |Cite
|
Sign up to set email alerts
|

Post-Emergence Movements and Overwintering of Snapping Turtle, <em>Chelydra serpentina</em>, Hatchlings in New York and New Hampshire

Abstract: Hatchling Common Snapping Turtles (Chelydra serpentina) were captured within, or as they emerged from, their nest cavities in Long Island, New York, and in southeastern New Hampshire. They were fitted with radiotransmitters and released at their nest sites. Their movements were monitored for as long as possible, which for some included tracking them to their overwintering sites and relocating them the following spring. On Long Island, all hatchlings initially moved to water. Later movements were both aquatic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
4
1
Order By: Relevance
“…We demonstrated that western pond turtle hatchlings occupied the nest chamber for up to almost 2 mo after initial emergence of siblings. The highly asynchronous emergence among siblings was contrary to the published literature on freshwater turtles that suggest either synchronous or near-synchronous emergence (,12-d interval) among siblings (Burger, 1976;Butler and Graham, 1995;Standing et al, 1997;Ultsch et al, 2007). Complicating the notion of timing of emergence, some individuals in our study re-entered their nest chambers, which may have been a behavioral response to periodic cold weather that is typical in western Oregon at the elevations of our study areas.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…We demonstrated that western pond turtle hatchlings occupied the nest chamber for up to almost 2 mo after initial emergence of siblings. The highly asynchronous emergence among siblings was contrary to the published literature on freshwater turtles that suggest either synchronous or near-synchronous emergence (,12-d interval) among siblings (Burger, 1976;Butler and Graham, 1995;Standing et al, 1997;Ultsch et al, 2007). Complicating the notion of timing of emergence, some individuals in our study re-entered their nest chambers, which may have been a behavioral response to periodic cold weather that is typical in western Oregon at the elevations of our study areas.…”
Section: Discussioncontrasting
confidence: 95%
“…Our observations that hatchlings entered shallow aquatic habitats with dense submerged vegetation and logs was consistent with observations that suggested these types of areas provide primary aquatic habitat for western pond turtle hatchlings (Reese, 1996;Buskirk, 2002) and many other species of freshwater turtles (Ultsch et al, 2007;Ernst and Lovich, 2009). Holte (1998) observed two hatchling western pond turtles opportunistically in small ephemeral bodies of water, such as in hoof-prints.…”
Section: Aquatic Habitatsupporting
confidence: 89%
See 1 more Smart Citation
“…S1). This expectation arises because hatchlings must emerge from nests and seek aquatic refugia before winter (Packard and Packard , Ultsch et al ), and snapping turtles also exhibit a longer average incubation duration and later first nest timing than painted turtles (Ernst and Lovich ). Yet, after accounting for temperature differences between locales, we found that ON snapping turtles had a higher reaction norm elevation (i.e., initiated nesting relatively later) than MI snapping turtles, even though reaction norm slope was similar between locales (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We currently lack available, standardized data at the individual and within-population scales, limiting our capacity for an among-population, global review of turtle headstarting. Empirical data on the behavior, ecology, and movement of wild juvenile turtles are extremely limited (Ultsch et al 2007;Paterson et al 2012;Whitear et al 2017), but necessary to inform best practices for release-site selection and release timing, as well as for the parameterization of population growth models evaluating headstarting. With advancements in tracking technology towards smaller and lighter tags, we can now follow hatchling turtles and obtain comparative, size-specific survivorship estimates from wild populations (e.g., Paterson et al 2012).…”
Section: Impacts Among Populationsmentioning
confidence: 99%